Hypertension and the Brain as an End-Organ Target - Girouard, Hélène (Springer International Publishing : Imprint: Springer, 2016)
The first comprehensive overview of the effects of hypertension on the brain. The book discusses not only the relationship between hypertension and stroke, but also the much less studied relationship between hypertension and cognitive decline and neurodegenerative diseases such as Alzheimer's. It seeks to answer two important questions. First, what are the conditions under which hypertension is associated with stroke, cognitive decline, and neurodegenerative disease? And second, what are the biological mechanisms by which hypertension alters brain homeostasis? By looking at the biological mechanisms of these relationships, this book provides insight to neuroscientists and neurologists regarding why anti-hypertension treatments make a big difference in the case of stroke, but have very little impact on cognitive decline and brain aging.